Increasing tumor targeting efficacy by nanomedicine - Khang, Dongwoo (Henry Stewart Talks, 2015)
Rationale: low target efficacy drugs, Physiochemical properties of nanoparticles, Mesenchymal stem cell-nanodrug delivery, Transportation to cancer organelles